2018
DOI: 10.1038/nrn.2018.2
|View full text |Cite
|
Sign up to set email alerts
|

Microglia in neuropathic pain: cellular and molecular mechanisms and therapeutic potential

Abstract: Acute nociceptive pain is a key defence system that enables the detection of danger signals that threaten homeostasis and survival. However, chronic pain (such as the neuropathic pain that occurs after peripheral nerve injury) is not simply a consequence of the continuity of acute nociceptive signals but rather of maladaptive nervous system function. Over recent decades, studies have provided evidence for the necessity and sufficiency of microglia for the alterations in synaptic remodelling, connectivity and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
543
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 619 publications
(582 citation statements)
references
References 194 publications
14
543
0
1
Order By: Relevance
“…4) The time course of the PNIinduced SDH microgliosis in mice was revealed to be that microglia number increased from day 3, peaked at 1 week and declined later, which is almost similar to the temporal pattern of microgliosis reported in previous studies. 11,25,26) Under such conditions, we clearly showed that a proliferation burst of SDH microglia occurred during the early phase (the first 3 d after PNI) but not during the later phase (at least until 2 weeks post-PNI).…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…4) The time course of the PNIinduced SDH microgliosis in mice was revealed to be that microglia number increased from day 3, peaked at 1 week and declined later, which is almost similar to the temporal pattern of microgliosis reported in previous studies. 11,25,26) Under such conditions, we clearly showed that a proliferation burst of SDH microglia occurred during the early phase (the first 3 d after PNI) but not during the later phase (at least until 2 weeks post-PNI).…”
Section: Discussionsupporting
confidence: 68%
“…Because a recent study has demonstrated that interrupting spinal microgliosis suppresses PNI-induced mechanical pain hypersensitivity and provided evidence that it is a crucial step in neuropathic pain, 11) the kinetics of microglial proliferation after PNI would also provide valuable information for developing a new therapeutic strategy. 4) In the present study we fully characterized the kinetics of microglial proliferation in the SDH after PNI and identified for the first time an unexpected narrow time window to rapidly induce a proliferation burst of SDH microglia after PNI.…”
mentioning
confidence: 99%
See 3 more Smart Citations